2007
DOI: 10.1161/01.hyp.0000257797.49289.71
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Circulating and Tissue-Based Renin-Angiotensin System in Preeclampsia

Abstract: Abstract-The renin-angiotensin system (RAS) participates in preeclampsia; however, the relative contributions from the circulating RAS and the tissue-based, uteroplacental RAS are unknown. We hypothesized that the tissue-based uteroplacental RAS is dysregulated in preeclampsia. We performed microarray and gene expression studies and confirmed the findings on the protein level by immunohistochemistry in ureteroplacental units from 10 preeclamptic women and 10 women with uneventful pregnancies. All of the women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
162
3
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(181 citation statements)
references
References 47 publications
10
162
3
5
Order By: Relevance
“…The interplay between ACE and ACE2 may govern the formation and metabolism of Ang effector peptides. No statistical difference was seen in the levels of ACE and ACE2 between normal and gestational hypertension, which is consistent with most previous studies [8,22,27], except the study of Ito et al, which reported significant increases in ACE mRNA and protein in the preeclamptic placenta. Reasons behind the difference are unclear.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The interplay between ACE and ACE2 may govern the formation and metabolism of Ang effector peptides. No statistical difference was seen in the levels of ACE and ACE2 between normal and gestational hypertension, which is consistent with most previous studies [8,22,27], except the study of Ito et al, which reported significant increases in ACE mRNA and protein in the preeclamptic placenta. Reasons behind the difference are unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Ang (1-7) is considered to have a counteracting effect to Ang II on the cardiovascular system by its inhibition of cell migration and proliferation [5,21,28]. Expression of AGT was found in our study, and no significant difference was found in the placenta of normal versus gestational hypertension, which was consistent with the study of Herse et al [8]. However, in the study of Lauren et al, AGT mRNA was higher in the chorionic villi obtained from preeclamptic subjects [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent study by Herse et al showed that AT1 receptor mRNA expression was 10-fold higher in the placenta than in the decidua tissues in both normal and preeclamptic pregnancies, but no difference was noticed for AT1 mRNA expression between normal and preeclamptic placental tissues [34]. In addition, AT1 autoantibody was also found in fetal serum in AT1 autoantibody positive mother complicated with preeclampsia [34]. However, whether AT1 autoantibody exerts any effects on AT2 receptor in VSMCs is not known.…”
Section: Discussionmentioning
confidence: 99%
“…AT1 plays important roles in angiogenic, inflammatory and oxidative stress responses in the placental vasculature [30][31][32][33]. A recent study by Herse et al showed that AT1 receptor mRNA expression was 10-fold higher in the placenta than in the decidua tissues in both normal and preeclamptic pregnancies, but no difference was noticed for AT1 mRNA expression between normal and preeclamptic placental tissues [34]. In addition, AT1 autoantibody was also found in fetal serum in AT1 autoantibody positive mother complicated with preeclampsia [34].…”
Section: Discussionmentioning
confidence: 99%